2014
DOI: 10.18352/jsi.423
|View full text |Cite
|
Sign up to set email alerts
|

Bridging social capital through sports: an explorative study on (improving) inter-ethnic contact at two soccer clubs in the Netherlands

Abstract: 46% (n=69) 38% (n=130) VV De Meern 7.9 (n=378) 8.5 (n=292) 7.6 (n=378) 8.3 (n=292) 12% (n=378) 10% (n=292) Total 7.7 (n=301) 7.9 (n=369) 7.9 (n=301) 7.5 (n=369) 24% (n=302) 29% (n=345) * "Aggression in my soccer club for some players is a reason to stop playing soccer". Table 3: Scores given to interaction between ethnic minority groups and people of Dutch origin of Zwaluwen and VV De Meern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 8 publications
2
9
0
4
Order By: Relevance
“…Following the challenges and problems of segregation throughout Western societies, often represented in media and policy articulation in relation to migration and the integration of minorities (Dahlstedt & Neergard, 2016), sport and leisure activities have been highlighted in social policy (as well as in scientific discourse) as an arena where social relations can be formed and social capital developed, in turn facilitating social inclusion and integration (Coalter, 2007;Collins & Haudenhuyse, 2015;Morgan, 2013;Spracklen, Long & Hylton, 2015;Verhagen & Boonstra, 2014). However, both the notions that sport and leisure activities are suitable means of promoting social relations and social capital (Coakley, 2011;Collins & Haudenhuyse, 2015) and that social capital leads to social integration (Blackshaw & Long, 2005), are contestable.…”
Section: Background and Social Policy Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the challenges and problems of segregation throughout Western societies, often represented in media and policy articulation in relation to migration and the integration of minorities (Dahlstedt & Neergard, 2016), sport and leisure activities have been highlighted in social policy (as well as in scientific discourse) as an arena where social relations can be formed and social capital developed, in turn facilitating social inclusion and integration (Coalter, 2007;Collins & Haudenhuyse, 2015;Morgan, 2013;Spracklen, Long & Hylton, 2015;Verhagen & Boonstra, 2014). However, both the notions that sport and leisure activities are suitable means of promoting social relations and social capital (Coakley, 2011;Collins & Haudenhuyse, 2015) and that social capital leads to social integration (Blackshaw & Long, 2005), are contestable.…”
Section: Background and Social Policy Contextmentioning
confidence: 99%
“…Although they emphasize bonding social capital, Verhagen and Boonstra (2014) underscore that participation in sport may also form an introduction to bridging relations in associations, with people in and around activities, when the social climate supports mutual and coequal social interaction. Similarly, Harvey, Lévesque and Donnelly (2007) stress that social capital development requires long-term involvement in activities in order for relations to develop and for networks to be established.…”
Section: The Potential Of Bonding Social Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…An important part of the results of these investigations has indicated that sport is a favorable element for the contexts related to the phenomenon of immigration. In concrete terms, these studies show that sport cooperates positively with: (a) the acquisition of social and cultural capital [20][21][22][23]; (b) maintaining cultural identity and cohesion around it [64]; (c) the interaction between "culturally different" [18,[24][25][26]; and (d) the creation of intercultural networks [27].…”
Section: Can Sport Help In the Social Inclusion Of The Immigrant Popumentioning
confidence: 99%
“…The specific literature on this matter indicates that sport offers important possibilities for the contexts that present immigrant population, because it favors: (a) the acquisition of social and cultural capital [20][21][22][23]; (b) the maintaining of cultural identity and cohesion around it [10]; (c) the interaction between "culturally different" [18,[24][25][26]; and (d) the creation of intercultural…”
Section: Introductionmentioning
confidence: 99%